Duck Eggshell Biosorbent for Indigo Carmine Removal: Kinetic, Isotherm, and Adsorption Mechanism Studies - Adewirli Putra; Wiya E. Fitri; Deswati Deswati; Desy Kurniawati; Lia Anggresani; Corry Handayani; Aster Rahayu (Universitas Tadulako, 2026)
Synthetic dye contamination from medical laboratory wastewater poses a growing environmental challenge, particularly from compounds such as indigo carmine, which are toxic, biologically recalcitrant, and detrimental to aquatic life. This research investigated duck eggshell as an eco-friendly, low-cost biosorbent for eliminating indigo carmine from medical laboratory effluents. The biosorbent was prepared by washing, oven-drying, grinding, and mild acid activation with 0.01 N HNO₃. Batch experiments were carried out by varying both the contact duration (15–60 min) and the initial dye concentration (10–50 mg/L), with residual concentrations determined using UV-Vis spectrophotometry. Adsorption kinetics were modeled using pseudo-first-order and pseudo-second-order equations, while equilibrium data were fitted to Langmuir and Freundlich isotherms. Peak adsorption capacity reached 8.20 mg/g within just 15 minutes of contact. The pseudo-second-order model gave the superior fit (R² = 0.9989), reflecting that surface-mediated interactions govern the process, though diffusion contributions cannot be excluded. Under optimal conditions, dye removal reached 67.80%, demonstrating efficient and rapid uptake. The Freundlich isotherm provided the best fit to the equilibrium data (R² = 0.9735), indicating multilayer uptake on an energetically heterogeneous surface. Overall, duck eggshell proved to be a practical, cost-effective, and sustainable material for removing dye pollutants from wastewater in the medical sector.